Injury Prevention News (IPN): a free e-newsletter for the UK and Ireland. (1st March 2011) - Verne, J; Brown, P; Slater, W; Towner, E; Bellis, M A; Anderson, Z; Hughes, K; Lyons, R A; Turner, S; Shepherd, J; Barron, S; Stone, D; et al.
Abstract : Injury Prevention News (IPN) is a free electronic newsletter produced jointly by the Injury Observatory for Britain and Ireland (IOBI; http://www.injuryobservatory.net ) and the Collaboration for Accident Prevention and Injury Control (CAPIC; http://www.capic.org.uk ). The purpose of IPN is to support injury prevention practitioners working in all areas of injury prevention and dealing with all age groups. IPN is a free source of information on new initiatives, statistical publications, research findings, forthcoming conferences and events, and also highlights new additions to the IOBI and CAPIC websites. Although IPN focuses on injury prevention work in the UK and Ireland, it also includes research from around the world. If you would like to receive IPN it can be downloaded freely from either the IOBI or CAPIC websites, or you can subscribe to IPN at the following web address http://www.injuryobservatory.net/sign_up.html . IPN currently has more than 200 people subscribed from around the world, with many organisations helping to promote IPN by including information in their own e-bulletins and newsletters. IPN is produced three times yearly with editions in January/February, May/June and October/November. For further information or to submit content towards the newsletter please contact Samantha Turner at s.turner@swansea.ac.uk .